The Use of Augmented Reality Based-Learning Media to Reduce Students' Misconceptions - Frelyana Tiro; Afadil Afadil (Jurnal Akademika Kimia, 2022)
The research objective is to determine whether using AR molecules as a learning medium can assist students in reducing their misconceptions about molecular materials. It was pre-experimental research with a one-group pre-test-post-test design. The average level of validity of the learning media used, according to the findings, is 70.3% ("valid" classification). The average reduction of misconceptions (MC) among students using learning media for the entire concept is 12.8 %, 9.2 % for students who do not understand the concept (DUC), and 22.0 % for students who understand the concept (UC). Based on these findings, it is possible to conclude that AR molecule-based learning media can be used to reduce students' misconceptions about molecular materials.